2022
DOI: 10.1111/1467-8551.12595
|View full text |Cite
|
Sign up to set email alerts
|

Stakeholder Green Pressure and New Product Performance in Emerging Countries: A Cross‐country Study

Abstract: Despite the burgeoning literature on stakeholder green pressure, research is scarce on how it influences eco-product innovation and new product performance. This article examines stakeholder green pressures as antecedents of eco-product innovation and new product performance in firms operating in resource-constrained countries. Using data gathered from surveys in Vietnam (N = 183) and Ghana (N = 217), we find that the positive effects of stakeholder green pressures on new product performance are serially media… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 30 publications
(29 citation statements)
references
References 118 publications
2
27
0
Order By: Relevance
“…In practice, manufacturing firms that incorporate green principles into their corporate market orientation must attempt to spend proportionately on GKM activities, and even greater expenditures may be required for GTI activities (Adomako et al, 2022). The results of this analysis have contributed to the realization that it is insufficient to merely adopt a green perspective as a strategic market direction.…”
Section: Discussionmentioning
confidence: 99%
“…In practice, manufacturing firms that incorporate green principles into their corporate market orientation must attempt to spend proportionately on GKM activities, and even greater expenditures may be required for GTI activities (Adomako et al, 2022). The results of this analysis have contributed to the realization that it is insufficient to merely adopt a green perspective as a strategic market direction.…”
Section: Discussionmentioning
confidence: 99%
“…resource‐constrained environments), the risk of ignoring stakeholder claims can directly influence a firm's survival (Adomako et al. , 2022; Bouguerra et al. , 2022).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
“…Traditionally, it has been suggested that stakeholder demands (Adomako et al. , 2022) – conditional on their salience in terms of power, urgency and legitimacy – influence how a firm responds to these demands (Mitchell, Agle and Wood, 1997). Specifically, a stakeholder's influence has been suggested to be a function of its legitimate and urgent claims as well as its power over other stakeholders (Frooman, 1999; Kochan and Rubinstein, 2000; Mitchell, Agle and Wood, 1997).…”
Section: Theoretical Background and Hypothesis Developmentmentioning
confidence: 99%
See 1 more Smart Citation
“…This shift has motivated several companies to integrate sustainability into their core business models, including employee training, supply chain management, and product development (Adomako & Tran, 2022c; Khizar et al, 2022; Porter & Kramer, 2011). Moreover, green products play an important role for entrepreneurial firms to effectively respond to stakeholder green pressures (Adomako et al, 2022). Thus, green product development, responsible innovation, and sustainability have increasingly become important corporate strategic issues for achieving competitive advantage (Albino et al, 2009; Chen, 2001; Dost et al, 2019).…”
Section: Introductionmentioning
confidence: 99%